2014
DOI: 10.1136/annrheumdis-2013-204769
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ascending methotrexate dose in combination with adalimumab: the randomised CONCERTO trial

Abstract: ObjectiveCONCERTO was a randomised, double-blind, parallel-armed study of methotrexate (MTX) in combination with adalimumab to assess whether an increasing trend of efficacy and decreased safety exists when increasing MTX dose in patients with early rheumatoid arthritis (RA).MethodsEarly, biologic and MTX-naive RA patients (N=395) were evenly randomised to open-label adalimumab (40 mg every other week) plus weekly blinded 2.5, 5, 10 or 20 mg MTX for 26 weeks. Clinical, radiographic and functional outcomes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
149
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(173 citation statements)
references
References 29 publications
14
149
0
10
Order By: Relevance
“…In MUSICA, we cannot rule out that persistent levels of polyglutamated MTX may have contributed to the lack of difference observed between the two MTX dosage groups for many of the PROs assessed. The findings in MUSICA are similar to those in the CONCERTO trial [19], where the initiation of treatment with a combination of adalimumab plus 2.5/5/10 or 20 mg/week MTX in treatment-naïve patients with early RA, led to similar improvements in a range of PROs including physical function, disease activity, sleep, and quality of life after 8 weeks [20]. The interpretation of the CON-CERTO results was not affected by prior MTX usage as it was in MUSICA, which was conducted in MTX-IR patients.…”
Section: Discussionsupporting
confidence: 76%
“…In MUSICA, we cannot rule out that persistent levels of polyglutamated MTX may have contributed to the lack of difference observed between the two MTX dosage groups for many of the PROs assessed. The findings in MUSICA are similar to those in the CONCERTO trial [19], where the initiation of treatment with a combination of adalimumab plus 2.5/5/10 or 20 mg/week MTX in treatment-naïve patients with early RA, led to similar improvements in a range of PROs including physical function, disease activity, sleep, and quality of life after 8 weeks [20]. The interpretation of the CON-CERTO results was not affected by prior MTX usage as it was in MUSICA, which was conducted in MTX-IR patients.…”
Section: Discussionsupporting
confidence: 76%
“…However, little is known about the minimally effective dose of MTX when used in combination with a TNF inhibitor in patients with RA. Recently, the CONCERTO trial demonstrated that 10 mg/week of MTX is a possible dosage for use in combination with TNF inhibitors (30). Moreover, the unique situation in Japan has provided interesting data showing that concomitant MTX of 7-8 mg/week works additively with TNF inhibitors (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Conventional synthetic DMARD-s applied in patients with RA decrease swelling of joints, reduce pain, lower the parameter values of acute phase of inflammation and improve joint function (21,(39)(40)(41)(42)(43)(44)(45).…”
Section: Therapeutic Strategies In Patients With Rheumatoid Arthritismentioning
confidence: 99%